Handbook of materials selection for engineering applications - Murray, G. T. 1927- (Mechanical engineering (Marcel Dekker, Inc.), 1997)
Reflecting the rapid advances in new materials development, this work offers up-to-date information on the properties and applications of various classes of metals, polymers, ceramics and composites. It aims to simplify the materials selection process and show how to lower materials and manufacturing costs, drawing on such sources as vendor supplied and quality control test data.